ACTIVITY-BASED PRINCIPLE IMPLEMENTATION IN THE METHODOLOGICAL CONCEPT OF N. E. JERGANOVA - N. K. Chapaev (Russian State Vocational Pedagogical University, 2016)
The aim of the publication is a philosophical-pedagogical conceptualization and the discovery of the mechanism of application of the principle while solving problems of program-methodological support of vocational education on the basis of summarizing the scientific heritage of N. E. Jerganova.Methods. The research is based on the hermeneutic methodology. The leading methods of analysis are the following: interpretation, conceptualization, understanding, as well as analysis, comparing, contrasting, synthesis, generalization.Results. Based on the analysis of the texts of the works of N. E. Jerganova, interpretational model of actualization principle of activity in developing methods of professional education is developed. According to this model, personal and professional development of man is attained primarily due to the actualization of his/her intellectual and creative potential, turning it into relatively self-sufficient entity of educational activity.Scientific novelty. Philosophical-methodological foundations and technological tools of the application of the principle activities in the process of problem solving of software and methodological support of professional education are disclosed; the expediency of development of activity-based strategy of professional education in modern conditions is proved.Practical significance. The thesis and conclusions of the article can be used in the development of the modern concept of methodological activities, in the process of program-methodological support of educational activity in professional education organizations.